Fade out - Suma, Nova Ren. (New York : Simon Pulse, 2012)
Imaginative thirteen-year-old Dani feels trapped in her small mountain town with only film noir at the local art theater and her depressed mother for company, but while trying to solve a real mystery she learns much about herself and life.
Previously titled: Dani noir.
Keywords: Motion pictures -- Fiction; Mothers and daughters -- Fiction; Divorce -- Fiction; Remarriage -- Fiction; Conduct of life -- Fiction; Mystery and detective stories